Can the parties to an international sale contract on CIF Incoterms varied in the oil and gas industry achieve the objective of linking the passing of ownership in the petroleum products that are sold from England to South Africa to the passing of risk in those petroleum products by indicating such intention in their contract of sale? - Cairncross- Chinnapyel, Nancy (Department of Commercial Law, 2015)
This dissertation aims to focus on whether the parties to an international sale contract on CIF Incoterms varied in the oil and gas industry, specifically the petroleum sector, achieve the objective of linking the passing of ownership in the petroleum products1 sold from England to South Africa, to the passing of risk in those petroleum products by indicating such intention in their contract of sale?